Detrital zircons U-Pb SHRIMP ages and provenance of La Modesta Formation, Patagonia Argentina - Moreira, Pilar (2013)
This paper summarizes the geology of the Paleozoic La Modesta Formation in Patagonia, Argentina, and presents new SHRIMP U-Pb dating of detrital zircons from muscovite-chlorite schist and tourmalinite. Also complementary geochemical and lead isotopic data are presented, indicating that the protoliths were formed from upper crustal rocks by the contribution of a large input from recycled (or felsic) sources. The maximum age of sedimentation of La Modesta Formation is about 446±6Ma. The basin closure (or eventually a paleocurrent shift) occurs at Lower Devonian before the exhumation of the Middle-Devonian granitoids of the Rio Deseado Complex (Deseado Massif). Many of the detrital zircons are igneous and record Ordovician ages, with a prominent Lower Ordovician-age peak at approximately 473Ma. Most favourable candidates to provide the younger zircons in the basin would Ordovician granites of the Rio Deseado Complex (Deseado Massif) and Punta Sierra Plutonic Complex (Somun Cura Massif). Older zircons have peaks of different importance (including Brasiliano and Grenvillian ages) between 530 and 700, 750-1500, 1750-2000 and 2550-2700Ma. La Modesta Formation is also a potential area of materials (detrital zircon) to the basin where the rocks of the Eastern Andean Metamorphic Complex and equivalent formations of the Andean region were generated.